The adoption and effect of artificial intelligence on human resources management - Tyagi, Pallavi; Chilamkurti, Naveen, 1974-; Grima, Simon; Sood, Kiran; Balusamy, Balamurugan (Emerald studies in finance, insurance, and risk management ;, 2023)
Emerald Studies In Finance, Insurance, And Risk Management 7 explores how AI and Automation enhance the basic functions of human resource management. The traditional framework of Human Resource Management (HRM) primarily consists of four functions: Human Resource Planning, Recruitment and Selection, Training and Development and Performance Management Systems which help businesses in hiring, motivating and retaining employees. The introduction of Artificial Intelligence (AI) has changed all of these aspects. The Adoption and Effect of Artificial Intelligence on Human Resources Management Series sets out a blended approach towards different functions of HRM and AI, reflecting upon: HR data privacy; data security; diversity and inclusion using AI; and sustainable AI-HR practices. This book is ideal for HR managers, senior managers, researchers, and students planning a career in this field.